Testing a Web-Based Food Ordering System with the Application of Geolocation - Satria Perdana Putra Prabowo; Ina Sholihah Widiati; Tinuk Agustin (PT FORMOSA CENDEKIA GLOBAL, 2023)
In the modern restaurant industry, there is intense competition to achieve customer satisfaction through Service Excellence or Service Differentiation. One service advantage that restaurants can offer is a Food Ordering System. The Self-Service Food Ordering System is a solution for restaurants to enhance the customer experience by providing the freedom to order food independently. It is crucial for restaurants to protect this system from external misuse, such as fraudulent orders that can cause financial losses. One solution that can be implemented is the utilization of Geolocation. Implementing Geolocation allows restaurants to obtain real-time user location data with the user's consent, thereby providing better protection for the self-service food ordering system. Testing is necessary to ensure the proper functioning of the system, including testing its features, compatibility, and the geolocation component.